2018
DOI: 10.1109/led.2018.2854541
|View full text |Cite
|
Sign up to set email alerts
|

Flexible IGZO TFT SPICE Model and Design of Active Strain-Compensation Circuits for Bendable Active Matrix Arrays

Abstract: The detailed measurement and characterization of strain induced performance variations in flexible InGaZnO thinfilm transistors (TFTs) resulted in a Spice TFT model able to simulate tensile and compressive bending. This model was used to evaluate a new concept, namely the active compensation of strain induced performance variations in pixel driving circuits for bendable active matrix arrays. The designed circuits can compensate the mobility and threshold voltage shifts in IGZO TFTs induced by bending. In a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…8(b). All three cases with the pixel circuit being laid flat, and under tensile strain and compressive strain showed a slight variation in the initial output current values due to mobility change under bending [18], [20]. After 24-hour bias stress, all the pixel circuits demonstrated the correct compensation behavior with less than ±1% variation (Fig.…”
Section: Measurement Results Of the 6t Pixel Circuitmentioning
confidence: 88%
See 2 more Smart Citations
“…8(b). All three cases with the pixel circuit being laid flat, and under tensile strain and compressive strain showed a slight variation in the initial output current values due to mobility change under bending [18], [20]. After 24-hour bias stress, all the pixel circuits demonstrated the correct compensation behavior with less than ±1% variation (Fig.…”
Section: Measurement Results Of the 6t Pixel Circuitmentioning
confidence: 88%
“…Previous reports [13], [18] have shown that, under tensile strain, the TFTs have slightly higher carrier mobility and much slower bias-induced degradation. On the other hand, when the TFTs are bent under compressive strain, they have slightly lower mobility and relatively faster bias-induced degradation.…”
Section: Impact Of the Applied Mechanical Strainmentioning
confidence: 85%
See 1 more Smart Citation
“…Although the tolerable tensile strain and minimum bending radius can be improved to 1.7% and 25 μm by using encapsulation layers [10], thin substrates [11], or ductile materials [12], circuits have to consider bending effects. Therefore a SPICE level 61 transistor model was modified to simulate the influence of strain [13].…”
Section: A Mechanical Strainmentioning
confidence: 99%
“…OLEDs are considered as one of the most promising next generation display technologies due to their superior performance such as high efficiency, wide viewing angle, low power and small thickness [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Recently, the oxide-based TFTs driving OLED have become the most promising technology to realize really flexible displays [34][35][36][37][38][39][40][41]. The technological advance in TFTs is a significant factor for promoting the development of such displays [42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%